Perbedaan Health Belief Model Berdasarkan Gender pada Mahasiswa Kedokteran - Rahmiyati, Rahmiyati; Safitri, Jehan; Yuserina, Firdha (Personifikasi: Jurnal Ilmu Psikologi, 2024)
Gender difference in individual health beliefs have been reported in many studies, however there were inconsistent studies resulted regarding the presence or absence of gender difference. Medical students as future doctors considered as role models in community. The lifestyle of a doctor not only affects themselves but also has a significant influence on their surrounding environment. The aim of this study was to determine the health belief model (HBM) difference based on gender among medical students. This study employed a quantitative cross-sectional research design. The subjects were medical students, consisting of 54 males and 57 females. Stratified random sampling was used for sampling. The measurement employed the Health Belief Model (HBM) scale developed by the researchers based on the six dimensions of HBM from Champion dan Skinner (2008). Data were analyzed using independent t-test. The results of this study indicated that there was no significant HBM difference based on gender. Both groups had good level of HBM. Based on the resulted, it can be concluded that there was no HBM difference based on gender among medical students.